The Effect of Service Quality on Customer Satisfaction of Sate H. Pardi Restaurant Branch Dr. M. Isa - Khorif Ma'ruf (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effect of service quality on customer satisfaction at Sate H. Pardi, Dr. M. Isa branch. Sampling employed incidental techniques. Data of 86 respondents were collected through questionnaires and interviews. This study applied a simple linear regression method to analyze the data. The result exhibits that service quality has a significant and positive effect on customer satisfaction. This research is advantageous forthe restaurant to enhance its business. To increase customer satisfaction, Sate H. Pardi, Dr. M. Isa branch should optimize its quality of service.